MITIGASI RISIKO DAN KLAIM ASURANSI PENGIRIMAN BARANGEKSPOR PADA PERUSAHAN INTERNASIONAL FREIGHT FORWARDER (Study Kasus pada PT. MSA Kargo Surakarta) - Handayani, Handayani; Sarjiyanto, Sarjiyanto (UI Scholars Hub, 2019)
This research it’s based on the intern study that beginner exporters were still do not understand about international trade risks and the mitigation. It has needed the role of freight Forwarder Company to assist in the delivery of export goods and get a guarantee for that delivery. MSA Cargo is a company bases in courier services for domestic and overseas, move fast-move safe is a work tenet in MSA Cargo. MSA Cargo do some innovation in export handling services by adding a risk analysis as well as mitigation to realize that tenet. This study told about the flow of risk management analysis and MSA Kargo’s role in mitigating the risk and mechanism for claims if there is a loss of export shipment. This research used descriptive-qualitative methode.The case was analysis of risk and export goods insurance claims via air by MSA Kargo as a company with the services which designated by exporter as their tenet. Results of this study can be concluded that the risks of export goods delivery were risk of payment and delivery.Risk mitigation analysis conducted MSA carried out through four stages: hazard identification, risk assessment, risk management and risk communication.The mechanism for exporter claims wasonly there is damage or loss of export goods delivery and then will be forwarded to the MSA. Finally its will covered by the insurance company as an insurer. The researcher gives suggestion to add context of buyer on risk analysis to prevent non-payment, MSA Kargo should empasizes the danger that could happen if it doesn’t mitigate early so the undesirable thing can not happen in the future.